2009
DOI: 10.1089/pho.2008.2327
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Facial Skin Cancer Treatment with High-Energy Pulsed Neodymium and Nd:YAG Lasers

Abstract: Neodymium laser irradiation is an effective method to treat facial skin cancer of stages T(1-2)N(0)M(0), and results in acceptable cosmetic results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 14 publications
0
26
0
3
Order By: Relevance
“…It is worthy to stress that radiation Nd laser as well as other types of lasers [11][12][13][14] does not cause resistance of tumor cells to this therapeutic modality and therefore it may be effectively used for successive sessions in case of recurrences of BCC after initial laser application and also limited BCC recurrences that appeared after other methods of treatment [22,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worthy to stress that radiation Nd laser as well as other types of lasers [11][12][13][14] does not cause resistance of tumor cells to this therapeutic modality and therefore it may be effectively used for successive sessions in case of recurrences of BCC after initial laser application and also limited BCC recurrences that appeared after other methods of treatment [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…The progress in treatment of skin carcinoma has been achieved after laser radiation was introduced into practice [11][12][13][14][15][16][17][18][19][20]. Previously we have shown that treatment of facial skin carcinoma by high-energy Nd laser radiation, resulted in deep destruction of tumors [21] and low recurrence rate [22,23]. In this paper the influence of morphological pattern, stage of disease, clinical features and accurate localization on the results of facial carcinoma treatment by Nd laser radiation are described.…”
Section: Introductionmentioning
confidence: 99%
“…Several treatment options for basal cell carcinoma have been described including surgical excision (Walker et al 2006), curettage (Barlow et al 2006) and cautery (Spiller et al 1984), cryotherapy (Mallon et al 1996, Kokoszka 2003, radiotherapy (AlOthman 2001), photodynamic therapy (Star et al 2006, Chapas et al 2006, Brathen et al 2007, micrographic surgery (Bieley et al 1992, Rowe et al 1989), ablative laser (Goldman and Wilson 1964, MacGuff 1966, Goldman et al 1968, Adams and Price 1979, Wheeland et al 1987, Fairhurst et al 1992, Grobbelaar et al 1997, Krunic et al 1998, Humpreys et al 1998, Horlock et al 2000, Nouri et al 2002, Campolmi et al 2002, Robinson et al 2003, and Smuckler et al 2008, other laser systems (El-Tonsy et al 2004, Moskalik et al 2009, Allison et al 2003, Campolmi et al 2008, Shah et al 2009, Konnikov et al 2011, Ibrahimi et al 2011, topical treatment with 5-fluorouracil and immunomodulators, such as imiquimod (Kagy andAmonette 2000, Schulze et al 2005) and intralesional agents as interferon (Greenway et al 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Local anesthesia is used and the operation lasts 2-3 times faster than ROMA, which reduces complications in postoperative period and ensures good cosmetic results, increasing the satisfaction of patient. Historically СО 2 and Nd:YAG lasers are used [7,8]. However they have many limitations.…”
Section: Introductionmentioning
confidence: 99%